Clinical features and independent predictors of postoperative refractory trauma to anal fistula combined with T2DM: A propensity score-matched analysis-retrospective cohort study - Tang, Xiao; He, Taohong; Li, Xinyi; Liu, Ya; Wu, Yuqi; You, Gehang; Li, Jie; Yun, Yu; Wu, Lei; Li, Li; Kang, Jian (Frontiers in Surgery, 2023)
Background: Refractory wound is a common postoperative complication in anal fistula surgery, when combined with type 2 diabetes mellitus (T2DM) it presents a slower recovery time and more complex wound physiology. The study aims to investigate factors associated with wound healing in patients with T2DM. Materials and methods: 365 T2DM patients who underwent anal fistula surgery at our institution were recruited from June 2017 to May 2022. Through propensity score-matched (PSM) analysis, multivariate logistic regression analysis was applied to determine independent risk factors affecting wound healing. Results: 122 pairs of patients with no significant differences were successfully established in matched variables. Multivariate logistic regression analysis revealed that uric acid (OR:1.008, 95%CI:1.002-1.015, p=0.012), maximal fasting blood glucose (FBG) (OR:1.489, 95%CI:1.028-2.157, p=0.035) and random intravenous blood glucose (OR:1.130, 95%CI:1.008-1.267, p= 0.037) elevation and the incision at 5 o’clock under the lithotomy position (OR:3.510, 95%CI:1.214-10.146, p=0.020) were independent risk factors for impeding wound healing. However, neutrophil percentage fluctuating within the normal range can be considered as an independent protective factor (OR:0.906, 95%CI:0.856-0.958, p=0.001). After executing the receiver operating characteristic (ROC) curve analysis, it was found that the maximum FBG expressed the largest under curve area (AUC), glycosylated hemoglobin (HbA1c) showed the strongest sensitivity at the critical value and maximum postprandial blood glucose (PBG) had the highest specificity at the critical value. To promote high-quality healing of anal wounds in diabetic patients, clinicians should not only pay attention to surgical procedures but also take above-mentioned indicators into consideration.